Anteseden dan Konsekuensi Pendidikan Kewirausahaan Berbasis Syariah, Studi Empiris Pada Fakultas Ekonomi UMN Al Washliyah - Reza Hanafi Lubis; Junita Putri Rajana Harahap; Mhd Dhani Habra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of the curriculum and Entrepreneurship courses makes universities, especially the Faculty of Economics, seek to develop Sharia-based Entrepreneurship education as a subject at the Faculty of Economics. However, the question of the effectiveness of the Entrepreneurship course for students of the Faculty of Economics is still an unanswered question. This research was conducted at the Faculty of Economics at UMN Al Washliyah with a population of students from the 2018-2019 Management and Accounting Study Programs and the 2019-2020 Accounting Study Program alumni with a systematic random sampling method of 50 samples. Data collection techniques used by conducting interviews and questionnaires digitally using google form. This study aims to see the extent to which entrepreneurship education, student creativity, entrepreneurial experience, entrepreneurial motivation and income expectations are related to student interest in entrepreneurship